2001
DOI: 10.1542/peds.108.6.e100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Administration of Activated Charcoal in the Home

Abstract: ABSTRACT. Objective. Activated charcoal (AC) is recognized as the treatment of choice for gastrointestinal decontamination after many ingestions. AC use in the home has been limited by concerns that parents would not administer it properly and that children would refuse to take AC. Previous descriptions of home administration have reported mixed results.Methods. This was an 18-month consecutive case series of all patients for whom AC administration was recommended in the home. Data collected included AC availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Home administration of activated charcoal to children by caregivers is interesting conceptually but has been met with contradictory results in practice. 11,12 In one study, none of 15 subjects were able to complete a therapeutic dose. In another, a case series based at the Kentucky Regional Poison Center found that home administration of charcoal could be achieved within 1 hour of ingestion in 95% of cases but in only 33% of those waiting for treatment in an emergency department.…”
Section: Timing Of Charcoal Administrationmentioning
confidence: 99%
“…Home administration of activated charcoal to children by caregivers is interesting conceptually but has been met with contradictory results in practice. 11,12 In one study, none of 15 subjects were able to complete a therapeutic dose. In another, a case series based at the Kentucky Regional Poison Center found that home administration of charcoal could be achieved within 1 hour of ingestion in 95% of cases but in only 33% of those waiting for treatment in an emergency department.…”
Section: Timing Of Charcoal Administrationmentioning
confidence: 99%
“…No evidence was found to suggest that activated charcoal is efficacious as a component of first aid for acute poisoning, although 2 small LOE 5 studies 14,15 suggest that it may be safe to administer. One LOE 3 study 16 demonstrated that the majority of children will not take the recommended dose of activated charcoal.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Two studies found a high acceptance rate (83-90%) in children offered AC [69, 70]. In contrast, Kornberg reported that only 21/70 (30%) of children in the ED with an ingestion voluntarily took oral charcoal; the rest received it by nasogastric tube [71].…”
Section: What Are the Risks Of Giving Activated Charcoal?mentioning
confidence: 99%